Dead giveaway ; Bewitched ; Soaring in the sky [videorecording] - Lazaro, Cheche (The Probe Team, 1994)
Tackles conflict within the leftist movement, death of Ka Hector upon order of Ka Roger, the head of the Melito Glor Command in the Southern Tagalog region. Investigates Siquijor Island as "Witchcraft Island." Also tackles balloning as a pastime and sport.